2018
DOI: 10.33549/physiolres.933637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increased Myocardial Tissue Concentration of Myristic, Palmitic and Palmitoleic Acids on the Course of Cardiac atrophy of the Failing Heart Unloaded by Heterotopic Transplantation

Abstract: The present experiments were performed to evaluate if increased heart tissue concentration of fatty acids, specifically myristic, palmitic and palmitoleic acids that are believed to promote physiological heart growth, can attenuate the progression of unloading-induced cardiac atrophy in rats with healthy and failing hearts. Heterotopic abdominal heart transplantation (HTx) was used as a model for heart unloading. Cardiac atrophy was assessed from the ratio of the native- to-transplanted heart weight (HW). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…It will also be noticed that a comparison of the degree of cardiac atrophy in the failing heart (the present study) and that observed in our recent study in the healthy (i.e. non-failing) heart [ 44 ] shows clearly that unloading-induced cardiac atrophy is distinctly more pronounced in the failing heart. These findings are critically important for at least two reasons.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It will also be noticed that a comparison of the degree of cardiac atrophy in the failing heart (the present study) and that observed in our recent study in the healthy (i.e. non-failing) heart [ 44 ] shows clearly that unloading-induced cardiac atrophy is distinctly more pronounced in the failing heart. These findings are critically important for at least two reasons.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, samples of LV myocardium were frozen in liquid nitrogen and stored at −80°C until analysis of the ‘fetal cardiac gene’ expressions, as described in detail previously. This was performed on days 7 and 28 after heterotopic HT x [ 44 ]. Briefly, the relative gene expression was calculated by the ΔΔ C t method and results were expressed as the n-fold difference in gene expression relative to β-actin mRNA of the transplanted-to-control heart (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This improvement was observed in the failing heart i.e. the one derived from animals with established advanced HF (Pokorný et al 2018b). Moreover, we have also found that the natural course of unloading-induced cardiac atrophy is different in the healthy and failing hearts (Pokorný et al 2018a).…”
Section: Introductionmentioning
confidence: 58%
“…the one derived from animals with established advanced HF (Pokorný et al 2018b). Moreover, we have also found that the natural course of unloading-induced cardiac atrophy is different in the healthy and failing hearts (Pokorný et al 2018a). On the whole, the basic question is whether an enhancement of isovolumic loading can be used as a general therapeutic approach to prevent or at least attenuate the development of unloading-induced cardiac atrophy.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation